Isolation and identification of constituents from the antitubercular DCM fraction from the leaf extract Premna odorata - Lirio, Stephen B.; Macabeo, Allan Patrick G.; Franzblau, Scott G.; Wang, Yuehong; Aguinaldo, Ma. Alicia M. (2011)
In recent years, the resurgence of multi- and extensively-drug resistant strains has prompted the need to develop safe drugs as quickly and efficiently as possible. In a preivous study, the dichloromethane sub-extract (PoMD) obtained from the leaf extract of the Philippine medicinal plant Premna odorata Blanco was found to be active against Mycobacterium tuberculosis H37Rv, exhibiting 99% inhibition at 128 μg/mL and 64 μg/mL concentrations. This study aims to purify the dichloromethane sub-extract and identify the constituents present therein. The PoMD extract was subjected to vacuum liquid chromatography (VLC) with gradient elution using hexane/dichloromethane and dichloromethane/methanol. Thin layer chromatograhic monitoring resulted in 20 pooled fractions which were bioassayed using Microplate Alamar Blue Assay (MABA). The fractions PoMD.4,5,7,8,9 and 15 were found to be active, having a minimum inhibitory concentration (MIC) of 53.87,119.71,117.12,113.12,82.80 and 108.91 μg/mL, respectively. The high yielding PoMD.8 was further subjected to VLC as above and gave 7 pooled fractions. PoMD.8.2 and PoMD.8.4 were further purified by column chromatgraphy with isocratic elution using hexane to obtain PoMD.8.2.1 and PoMD.8.4.1 as white flakes. Both isolates where characterized by spectroscopic methods and were found to be a mixture of β-sitosterol and stigmasterol. Purification of the other fractions is ongoing.
Keywords: Medicinal plants; Tuberculosis